MICHEL MOUSKHELY – ON THE ESTABLISHMENT OF THE COUNCIL OF EUROPE AND VISA-FREE TRAVEL TO EUROPE - Edisher Japharidze; Vazha Shubitidze (International Journal of Innovative Technologies in Social Science, 2021)
The European integration processes is not losing its topicality to this day. It still remains as the important political challenge of the 21st century in the geopolitical area of the modern world. In these processes Georgia is actively participating today too, as it is known an agreement of the association between Georgia and the European Union was signed in summer 2014. This fact was a landmark of the greatest historical importance for Georgian people. It means returning of the Georgian people to its initial homeland-Europe, which always struggled and strived for it. It must be noted that we are not entering the Europe with empty hands but are widely credited with the propaganda of European qualities and bringing them to Georgia. It is still not widely known to the general public that at the starting point of uniting the European Union (European Confederation) were standing famous Georgian scientists and public figures. M. Muskhelishvili and A. Nikuradze. While Robert Schuman and Jean Monnet talked about the idea of uniting Europe, M. Muskhelishvili and A. Nikuradze were publishing articles on the same subject in the leading newspapers and magazines and actively participated in the processes of creating the European Union.